Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3109/00207454.2013.879581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ebselen on ischemia/reperfusion injury in rat brain

Abstract: Ebselen has neuron-protective effects due to its antioxidant properties as shown by the decrease in MDA overproduction, increase in SOD activity and the histological improvement after administration of Ebselen to I/R in brain tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 30 publications
4
7
0
Order By: Relevance
“…However, the 30 mg/kg dose of ebselen did not significantly increase antioxidant enzyme activities. Our results were consistent with previous studies [21][22][23]30,31]. Therefore, we suggest that the protective effects of the 15 mg/kg dose of ebselen may be exerted via improvement of the antioxidant defense system in sciatic nerve I/R injury.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the 30 mg/kg dose of ebselen did not significantly increase antioxidant enzyme activities. Our results were consistent with previous studies [21][22][23]30,31]. Therefore, we suggest that the protective effects of the 15 mg/kg dose of ebselen may be exerted via improvement of the antioxidant defense system in sciatic nerve I/R injury.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the 30 mg/kg dose of ebselen significantly increased LPO accumulation compared with the sham group. The results of this study were consistent with previous studies [21][22][23]. Consequently, while the 15 mg/kg dose of ebselen pretreatment may be protective against sciatic nerve I/R injury by reducing LPO, the 30 mg/kg dose of ebselen appears to have little or no effect on LPO.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of available inhibitors of this redox system are directed toward TrxR, but recently, specific inhibitors of Trx have been tested in humans: PX-12 is under clinical trial as and anticancer agent (Baker et al, 2013;Kirkpatrick et al, 1998;Ramanathan et al, 2011), and ebselen is under investigation as a postischemia and poststroke therapeutic (Aras et al, 2014;Yamaguchi et al, 1998;Zhao et al, 2002). PX-12 and ebselen (EBS) inhibit the BoNT/A-induced cleavage of SNAP25 in CGNs as detected by immunofluorescence ( Figure 3A) and by quantitative immunoblotting ( Figure 3B).…”
Section: Inhibitors Of Thioredoxin Prevent the Intoxication Of Neuronmentioning
confidence: 99%
“…Therefore, in the present study, these two test compounds were each investigated separately and in combination for their ability to reduce the dermatoxicity of HN2. EB-1 is an anti-inflammatory antioxidant compound that is under investigation for reperfusion injury ( Aras et al, 2014 ), stroke ( Yamaguchi et al, 1998 ), hearing loss ( Kil et al, 2021 ) and bipolar disorder ( Singh et al, 2013 ). Previous research in our lab has shown the edema-reducing and anti-vesicant ( Lulla et al, 2014 ), anti-bacterial ( Chan et al, 2007 ), anti-fungal ( Billack et al, 2010 , Orie et al, 2017 ) and cyto-protective ( Hardej and Billack, 2007 , Pino and Billack, 2008 , Pino et al, 2013 ) properties of EB-1.…”
Section: Discussionmentioning
confidence: 99%